Spontaneous Involution of Pineal Cyst in an Infant - J Gordon Millichap (Pediatric Neurology Briefs, 2006)
A full-term newborn girl presenting at birth with macrocephaly and a large pineal region hemorrhagic cyst without neurologic deficit is reported from the University of Miami Miller School of Medicine, Florida.